Promoting general and specific self-efficacy beliefs by experiential education programs in the outdoors - Markus, Stefan; Eberle, Thomas; Fengler, Janne (8th SELF Biennial International Conference, 2015)
Transfer effects of experiential education programs depend on the participants' perceived level of challenges (Eberle, 2008). Different types of challenges, peak and limit experiences (Fengler, 2010) may influence sub-dimensions of self-efficacy beliefs (Schmitz, 2002). The aim of our study is to evaluate the structure of general and specific self-efficacy beliefs, their antecedents and development in an outdoor-educational setting. Positive effects are assumed on all self-efficacy sub-dimensions depending on the particular perceived level of challenge and the appraisal of success. Furthermore, we investigate the emotional experiences of participants during the intervention as well as interaction effects with achievement motives, risk and competition seeking, domain-specific values and self-efficacy beliefs. In our study, N=544 students from German secondary schools (8th to 11th grade) were asked by questionnaire before and after a one-week outdoor-educational intervention about certain beliefs (traits). Additionally, we measured their emotions and on-task-beliefs (states) after three randomly selected adventure educational tasks. Research is in progress. First findings show acceptable to good reliabilities of the scales. General, emotional and cognitive self-efficacy beliefs show significant increases. Positive emotions correlate positively with self-efficacy increase on a significant low to medium level. Implications for experiential education programs as well as school education will be discussed.
Keywords: Outdoor Education; Erlebnispädagogik; Selbstwirksamkeit; Self-efficacy